Inaugural Speech: Comparative Analysis of Inaugural Speech of Putin and Trump - Hres, Maryia (LANGUAGE ART, 2023)
The paper deals with an inaugural speech which is considered a type of political discourse. It overviews the definition of an inaugural speech and its distinctive features. As well, it studies the linguistic means which are used to strengthen the credibility of the inaugural speech and to increase its impact on public. The research focuses on the relation between the political programme of a president-elect and his inaugural speech, and hypothesizes that the political programme of a president-elect has a great influence on his inaugural speech production, mainly on the choice and distribution of linguistic means. In order to prove this hypothesis a comparative study of two inaugural speeches was carried out: the inaugural speech of V. Putin (2018) and D. Trump (2017).